Pengaruh Persepsi Kesejahteraan Guru dan Lingkungan Keluarga Terhadap Minat Menjadi Guru - Sheva Audina Maylasari; Durinda Puspasari (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study aims to analyze the influence of teacher welfare perception and family environment on students' interest in becoming teachers. This study employed an explanatory research design with a quantitative approach. The research sample consisted of all students from the 2022 cohort of the Office Administration Education Study Program, selected using the Proportional Random Sampling technique. Data were collected through a questionnaire. The data were analyzed using multiple linear regression with SPSS version 25. The findings indicate that (1) teacher welfare perception has a positive and significant effect on students' interest in becoming teachers, (2) family environment has a positive and significant effect on students' interest in becoming teachers, (3) teacher welfare perception and family environment simultaneously have a positive and significant effect on students' interest in becoming teachers among students of the Office Administration Education Study Program at Universitas Negeri Surabaya.